Testing Weak Exogeneity in Cointegrated Panels - Moral-Benito, Enrique; Serven, Luis (World Bank Group, Washington, DC, 2014)
For reason of empirical tractability, analysis of cointegrated economic time series is often developed in a partial setting, in which a subset of variables is explicitly modeled conditional on the rest. This approach yields valid inference only if the conditioning variables are weakly exogenous for the parameters of interest. This paper proposes a new test of weak exogeneity in panel cointegration models. The test has a limiting Gumbel distribution that is obtained by first letting the time dimension of the panel go to infinity and then letting its cross-sectional dimension go to infinity. The paper evaluates the accuracy of the asymptotic approximation in finite samples via simulation experiments. Finally, as an empirical illustration, the paper reports tests of weak exogeneity of disposable income and wealth in an aggregate consumption equation.